Awrah and Women's Clothing: Reinterpretation of Islamic Texts in Indonesian Contexts - Nikmatullah, Nikmatullah (Universitas Nurul Jadid, 2023)
The concept of Awrah among Indonesian Muslims undergoes a process of contextualization and adaptation to local culture. This article focuses on the understanding of the ulemas about Awrah based on the interpretation of Al-Quran and Hadith texts which have implications for the practice of women's clothing. By using a qualitative approach, data obtained from online media and interviews. This article shows that the models, forms and trends of women's clothing influenced by multiple interpretations of Islamic texts, which are not only influenced by religious understanding, modernity, local traditions but also the context of the relationship between Islam and the state. There has been a shift in the reasons women cover their private parts from piety and obedience in religion; security, comfort and tranquility; then a lifestyle. External factors that influence women to cover their awrah are due to the family and friends, as well as maintaining local traditions. Interestingly, women who choose not to cover their awrah have the support of religious prominent, with argumentation personally and religiously. There are attempts to reinterpret the spirit of Awrah which does not only focus on women's clothing, but includes issues of ethics, morals, decency and protection of women.